An equivalent spherical charge conversion (ESCC) approach for prediction of ground vibration due to blasting. (3rd April 2017) - Pal Roy, Pijush
Abstract: Peak particle velocity generated by cylindrically-charged blastholes fired at different delay detonators in surface blasting can be predicted with reasonable degree of certainty by an equivalent spherical charge conversion (ESCC) approach wherein the cylindrical charges are replaced by equivalent spherical charges. The validity of this conversion model has been tested through different predictive equations using experimental data of two opencast mines viz. Bhelatand Amalgamated Colliery and Joribahal Iron Ore Mine. In deriving these equations both maximum charge per delay and total charge fired in the round were considered separately. The results show that ESCC approach can be used as a reliable vibration prediction tool in surface blasting.